Photocatalysis-Assisted Process of Reusable PVA/TiO2 Nanofibers - Kusumaatmaja, Ahmad; Nugraheni, Ari Dwi; Purnawati, Diki; Rohmatillah , Ani; Nur Mahardika, Dian (Trends in Sciences, 2024)
Photocatalysis-assisted PVA/TiO2 nanofibers has become a prospective technology for water filtration applications. In line with this application, swelling behavior, photocatalytic activity and reusability are crucial considerations. This work presents the evaluation of swelling behavior and photocatalytic activity of PVA/TiO2 nanofibers in harsh pH environment. By varying pH environment at pH = 1 - 12, we have successfully shown that pH = 7 is the best environment for the PVA/TiO2 nanofibers-based water filtration. On this environment, the nanofibers has 92 % degradability and is able to resist Methylene Blue (MB) solution for up to 5 min. Likewise, it shows excellent reusability over 5 cycles usage. Moreover, the nanofibers is prospective for rapid filtration in harsh pH environment. This work is a step forward toward environmental-friendly water filtration in harsh pH environment. HIGHLIGHTS Study of photocatalysis-assisted PVA/TiO2 nanofibers for environmental-friendly water filtration. Discover superb degradability up to 98 % within 5 min application in Methylene Blue solution. Perform superior reusability up to 5 cycles usage. Highly prospective for harsh pH environment water filtration. GRAPHICAL ABSTRACT